The Government's Role in the Dissolution of PKI: A Legal and Human Rights Perspective - Maulana, Afan Husni; Maulana, Diky Faqih (UIN Sunan Kalijaga Yogyakarta, 2023)
The Dissolution of the Indonesian Communist Party (PKI) has been a matter of concern due to the restriction of the right to associate. On the other hand, the strict prohibition of the PKI's existence is intended to protect individual rights. The communist ideology emerged from the West as a response to the oppression of the bourgeoisie against the proletariat, aiming to establish an authoritarian state while prioritizing welfare. The teachings of the PKI are in conflict with Pancasila as the state philosophy and legislation due to differing state backgrounds. Therefore, it is not appropriate to implement them within the government system, as it poses a threat if the PKI's efforts to seize power were successful. So, what is the government's role in the dissolution of the PKI with a legal and human rights approach? This study employs a normative juridical research method. The research results indicate that the government issued regulations through the MPRS Decree to dissolve the PKI and prohibit the propagation of Marxist-Leninist ideologies in Indonesia. In this context, the government, as a duty bearer, has three obligations. First, to respect means that the PKI and Marxist-Leninist ideologies are strongly prohibited in Indonesia as a sign of the state's respect for the rights of the majority of the population. Second, to protect means that the state guarantees the rights of its citizens by banning the dissemination of communist ideologies, which pose a threat to the citizens' rights as communism does not recognize individual rights. Third, to fulfill means that the MPRS Decree banning the PKI and communist ideologies aims to make the state more democratic by not limiting or reducing citizens' rights, thus ensuring the fulfillment of citizens' rights in a democratic society